Teori Komunikasi dalam Perspektif Mazhab Frankfurt - Surahman Surahman (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2005)
Frankfurt School of Thought, which rooted in Marxism and Critical paradigm, provided many ways to interpret the meaning of communication. This school of thought is primarily based on the main tenets of Critical Theory, i.e. totality, consciousness, anomie, and critic. Some questions arise concerning the ontology, epistemology, and axiology dimensions of Frankfurt School of Thought. Ontology discussion concerning the nature of communication involved an intensive outlook of Giddens’s Structuration Theory. Epistemology involved a discussion with Gramscian concepts of hegemony. Meanwhile, the problem of axiology is best addressed in Habermas fashion of agent-structur-dialectics.